2011
DOI: 10.1007/s00420-011-0680-1
|View full text |Cite
|
Sign up to set email alerts
|

Acts of offensive behaviour and risk of long-term sickness absence in the Danish elder-care services: a prospective analysis of register-based outcomes

Abstract: Results indicate that prevention of threats, violence, and bullying may contribute to reduced sickness absence among elder-care staff. The results furthermore suggest that work organizations must be attentive on how to handle and prevent acts of offensive behaviour and support targets of offensive behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 37 publications
2
60
0
2
Order By: Relevance
“…With the exception of one study from Belgium (44), all included studies originated from Nordic countries (Denmark, Finland, Norway, and Sweden). Thirteen studies had a prospective research design and included registry data on sickness absence (36)(37)(38)(39)(44)(45)(46)(47)(48)(49)(50)(51)(52). Two studies used a retrospective design with registry data on sickness absence (31,53).…”
Section: Descriptive Findings and Assessment Of Methodological Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…With the exception of one study from Belgium (44), all included studies originated from Nordic countries (Denmark, Finland, Norway, and Sweden). Thirteen studies had a prospective research design and included registry data on sickness absence (36)(37)(38)(39)(44)(45)(46)(47)(48)(49)(50)(51)(52). Two studies used a retrospective design with registry data on sickness absence (31,53).…”
Section: Descriptive Findings and Assessment Of Methodological Qualitymentioning
confidence: 99%
“…Four studies were based on nationwide representative samples of the working population (36,38,39,54), whereas one study included data representative of a county (50). Seven studies included respondents from healthcare occupations (37,45,47,49,52,53,55). The remaining five studies were based on public employees (46,51), employees in an urban municipality (48), postal employees (31), and employees from mixed occupational groups (44).…”
Section: Descriptive Findings and Assessment Of Methodological Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…weekly or daily) exposure. It is established that workplace bullying adversely impacts employees in several ways (see Nielsen and Einarsen 2012;Nielsen et al 2014 for reviews), including outcomes such as physical and mental health problems Hansen et al 2011;Høgh et al 2011bHøgh et al , 2012bKivimӓki et al 2003;Tuckey and Neall 2014), low job-related well-being (Bowling and Beehr 2006;Djurkovic et al 2008;Rodríguez-Muñoz et al 2009), job turnover (Clausen et al 2013;Høgh et al 2011a), professional dropout (Høgh et al 2012a) and sickness absence (Clausen et al 2012;Kivimäki et al 2000;Ortega et al 2011). …”
Section: Introductionmentioning
confidence: 97%
“…For instance that exposure to bullying behaviour such as nasty teasing may generate both early and long-term stress reaction as shown in a 5-year follow-up study of the Danish working population; and that being bullied during your education may have health effects one year later as demonstrated by a prospective study of health care workers in care of the elderly (Høgh et al, 2007). Finally, longitudinal studies have also shown an increase in sickness absence among bullied targets (Clausen et al, 2011;Kivimäki et al, 2000;Ortega et al, 2011), as well as a risk of ending up on early retirement pension (Dellve et al, 2003) According to transactional stress models, the nature and severity of emotional reactions following exposure to bullying may be a function of a dynamic interplay between event characteristics and individual appraisal-and coping processes. Definitions of bullying at work commonly entail descriptions that emphasize prolonged exposure to interpersonal acts of a negative nature, with which the target is unable to cope.…”
Section: Early Indicators Of Psychosocial Work Environment and Healthmentioning
confidence: 99%